Reducing Delusional Conviction through a Cognitive-Based Group Training Game: A Multicentre Randomized Controlled Trial - Khazaal, Yasser; Chatton, Anne; Dieben, Karen; Huguelet, Philippe; Boucherie, Maria; Monney, Gregoire; Lecardeur, Laurent; Salamin, Virginie; Bretel, Fethi; Azoulay, Silke; Pesenti, Elodie; Krychowski, Raoul; et al. (Frontiers in Psychiatry, 2015)
Abstract Objective: “Michael’s Game” is a card game targeting the ability to generate alternative hypotheses to explain a given experience. The main objective was to evaluate the effect of MG on delusional conviction as measured by the primary study outcome: the change in scores on the conviction subscale of the Peters Delusions Inventory (PDI-21). Other variables of interest were the change in scores on the distress and preoccupation subscales of the PDI-21, the Brief Psychiatric Rating Scale, the Beck Cognitive Insight Scale, and belief flexibility assessed with the Maudsley Assessment of Delusions Schedule. Methods: We performed a parallel, assessor-blinded, randomised controlled superiority trial comparing treatment as usual plus participation in Michael’s Game (MG) with treatment as usual plus being on a waiting list (TAU) in a sample of adult outpatients with psychotic disorders and persistent positive psychotic symptoms at inclusion. Results: The 172 participants were randomised, with 86 included in each study arm. Assessments were performed at inclusion (T1: baseline), at 3 months (T2: post-treatment), and at 6 months after the second assessment (T3: follow-up). At T2, a positive treatment effect was observed on the primary outcome, the PDI-21 conviction subscale (p=0.005). At T3, a sustained effect was observed for the conviction subscale (p=0.002). Further effects were also observed at T3 on the PDI-21 distress (p=0.002) and preoccupation subscales (p=0.001), as well as on one of the MADS measures of belief flexibility (“anything against the belief”) (p=0.001). Conclusions: The study demonstrated some significant beneficial effect of MG. http://www.controlled-trials.com/ISRCTN37178153/ Funding: Swiss National Science Foundation Grant 32003B-121038